Analysis of interactive manufacturing systems: Towards a performance‐based assessment methodology. Issue 4 (14th September 2022) - Mulet alberola, Jose Antonio; Fassi, Irene
Abstract: Current manufacturing systems are forced to meet the most dynamic market demands under sustainable factors. However, not only technical transformations will address the challenge but, to fully cover social needs, the analysis of the human role in highly interactive systems is still decisive, following a socially sustainable approach. To fully extract the most from both agents under a performance point of view, the main added value of agents in the work environment needs to be carefully analysed, captured, and boosted. The context shapes a specific operation or task, which consequently drives the final outcome according to individual necessities. Furthermore, a methodology that potentially helps a proper assessment of these performance‐based interactions is still missing. The contribution focusses on the definition of a novel human‐centric methodology under a holistic point of view to analyse performance‐based interactions and to define appropriate indices and metrics that helps assessing the human‐system interactions in the manufacturing domain. The methodology is applied in a case study to guide practitioners with its use.